KREATIVITAS MAHASISWA PADA MATA KULIAH TATA RIAS FOTO/TV/FILM DAN KARAKTER DI JURUSAN TATA RIAS DAN KECANTIKAN - Indah Melia Gusrita. K (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
This research background is the importance of creativity in learning MakeUp Characters in order to produce extraordinary works based on the character of the character who wants to appear. The purpose of this research was to find out student creativity when viewed from the creative person in learning MakeUp Characters in make up and beauty department in terms of fluency, flexibility and authenticity. This research is descriptive research with quantitative approach. The research population was students majoring in make upy and Beauty class 2016 sessions A and B. The sampling technique is done by total sampling technique. The data analysis technique is done by determining the frequency distribution and determining the level of achievement of respondents, then categorizing the creative person through the value of the respondents' achievement based on the value classification. The results of the data show that the average student creativity in make-up learning characters in terms of fluency is 49.38 with the most categories at the moderate level of 26 people (59.1%). Dexterity average is 47.02 with the most category at the moderate level, which is 20 people (45.5%). The average authenticity is 46.11 with the most categories at a good level of 20 people (45.5%).